Managing Inter-Subject and Inter-Level Teacher Collaboration for Integrated Learning - Muhammad Yusron Maulana El-Yunusi; Nadif Sidqi; Ainurrozikin Ainurrozikin; Didit Darmawan; Imam Saroni (UIN Fatmawati Sukarno Bengkulu, 2026)
Background: Technological advancements in the modern era have had a significant impact on education by providing easier access to information while simultaneously posing new challenges for the character development of the younger generation. The current moral crisis, manifested through problematic behaviors, indicates a weak internalization of religious values and a lack of synergy between educational institutions, families, and society. Therefore, this study analyzes the role of Islamic Religious Education (PAI) in shaping the character of the Muslim generation amidst modernization and identifies the challenges arising from digital technology.Method: This study employs a library research methodology by reviewing relevant academic literature, including journals, books, and scientific reports. This approach facilitates a deep understanding of the research topic, theoretical analysis, and the formulation of logical conclusions regarding the function of PAI in character formation.Results: Research findings indicate that PAI plays a central role in shaping Islamic character through the internalization of values such as honesty, discipline, responsibility, and tolerance. PAI also functions as a moral fortress protecting youth from the negative impacts of technology, including diminished empathy and spiritual degradation. However, there are obstacles in the form of weak application of moral values in learning and a lack of synergy between schools, families, and society. Although digital technology offers opportunities through virtual platforms, uncontrolled use remains at risk of causing a moral crisis, thus requiring wise integration that maintains alignment with Islamic values.Conclusion: PAI has an essential role in forming Muslim personalities with a deep spiritual understanding while protecting students from the negative impacts of the modern era through comprehensive Islamic teachings. Despite facing challenges related to the lack of ethical approaches and environmental influences, PAI must adapt to contemporary developments to maintain Islamic identity and cultivate a faithful generation with noble character.